Sustainability Practices and Financial Outcomes: Exploring the Role of Carbon Emission Disclosure - Riadi, Sugeng; Enzan Rahmadani, Nur (Akuntansi & Ekonomika, 2026)
This research examines the factors and financial consequences of carbon emission disclosure in relation to company sustainability policies. It specifically investigates the degree to which media exposure, environmental performance, ISO 14001 certification, and social performance impact carbon emission disclosure, and how this disclosure subsequently influences firms' financial success. We used a quantitative study approach and secondary data from the annual and sustainability reports of manufacturing companies on the Indonesia Stock Exchange from 2019 to 2023. After applying the criterion for data completeness, 135 firm-year observations were included in the final sample. The data were examined with the PLS-SEM methodology. The findings indicate that carbon emission disclosure positively and significantly influences financial performance, whereas media exposure, environmental performance, ISO 14001 certification, and social performance exert no impact on carbon emission disclosure